Differences Between Snakebites with Concomitant Use of Alcohol or Drugs and Single Snakebites. Issue 2 (February 2018) - Schulte, Joann; Kleinschmidt, Kurt C.; Domanski, Kristina; Smith, Eric Anthony; Haynes, Ashley; Roth, Brett
Abstract : Objectives: Published reports have suggested that the concurrent use of alcohol or drugs occurs among some snakebite victims, but no national assessment of such data exists. Methods: We used data from US poison control centers collected during telephone calls in calendar years 2000–2013 to compare snake envenomations with concomitant use of drugs, alcohol, or both to snakebites lacking such use. Results: A total of 608 snakebites with 659 instances of concomitant alcohol/drug use were reported, which represent approximately 1% of 92, 751 snakebites reported to US poison control centers. An annual mean of 48 snakebites with concomitant use of alcohol/drugs was reported, compared with a mean of 6625 snakebites per year with no concomitant use of alcohol/drugs. Most cases involved men, peaked during the summer months, and involved copperheads or rattlesnakes, which mirrored overall trends. Snakebite victims who also used alcohol/drugs were more likely than victims with only a snakebite reported to be bitten by rattlesnakes, to be admitted to the hospital, and die. Alcohol was the most common reported concomitant substance, but other substances were reported. Conclusions: Snakebites with concomitant use of alcohol/drugs are uncommon, accounting for approximately 1% of the snakebite envenomations reported annually to US poison control centers; however, snakebite victims also reporting alcohol/drug use are more likely to be bitten by rattlesnakes, be admitted to a healthcare facility, and die. Abstract : This article uses poison control center data to describe the 1% of snakebite victims who report concurrent use of alcohol/drugs and compares that group with victims who report snakebite only. The two groups are similar in that most victims are boys and men and the rates peak in the summer months. Snakebite victims reporting concurrent use of alcohol are more likely to be bitten by rattlesnakes and die.